Digital fabrication of flanges in removable partial dentures: a step-by-step workflow - Abdul Hamid, Nor Faharina; Yacob, Norlela; Shuib, Solehuddin; Ahmad, Rohana (IIUM Journal of Orofacial and Health Sciences, 2025)
The fabrication of flanges in removable partial dentures (RPD) traditionally entails labour-intensive manual manipulation of materials such as wax to sculpt and shape the flanges according to the patient’s oral anatomy. This method requires a high level of skill and precision from dental technicians to ensure the final prosthesis fits comfortably and functions effectively. While most RPD framework designs are now executed digitally, the arrangement of artificial teeth and flanges often remains a manual process. This is primarily due to the scarcity of suitable software capable of designing flanges using computer-aided design (CAD) technology. This report addresses this challenge by presenting an alternative approach to flange design using the CAD software of 3Shape Dental System. By utilizing the software’s function for custom tray design, we developed the flanges with the aid of abutment teeth, artificial teeth and framework, thereby improving the accuracy of gingival anatomy in flange fabrication.